Anoxic spreading depolarization in the neonatal rat cortex in vitro - Gainutdinov, Azat; Juzekaeva, Elvira; Mukhtarov, Marat; Khazipov, Roustem (Frontiers in Cellular Neuroscience, 2023)
Anoxic spreading depolarization (aSD) is a hallmark of ischemic injury in the cerebral cortex. In adults, aSD is associated with rapid and nearly complete neuronal depolarization and loss of neuronal functions. While ischemia also evokes aSD in the immature cortex, developmental aspects of neuronal behavior during aSD remain largely unknown. Here, using oxygen-glucose deprivation (OGD) ischemia model in slices of the postnatal rat somatosensory cortex, we found that immature neurons displayed much more complex behaviors: they initially moderately depolarized during aSD, then transiently repolarised (for up to tens of minutes), and only then passed to terminal depolarization. The ability to fire action potentials was maintained in neurons mildly depolarized during aSD without reaching the level of depolarization block, and these functions were regained in the majority of immature neurons during post-aSD transient repolarization. The amplitude of depolarization and the probability of depolarization block during aSD increased, whereas transient post-SD repolarization levels and duration, and associated recovery in neuronal firing decreased with age. By the end of the first postnatal month, aSD acquired an adult-like phenotype, where depolarization during aSD merged with terminal depolarization and the phase of transient recovery was lost. Thus, changes in neuronal function during aSD undergo remarkable developmental changes that may contribute to lower susceptibility of the immature neurons to ischemia.